Emotional intelligence and its relationship to the ranking of players' results on the floor exercise mat in artistic gymnastics - Mohamed, Asst.L. Noor Essam (Sulaimani Journal for Humanities, 2026)
The current study aims to identify the concept of emotional intelligence in psychology, as individuals with consistent emotional intelligence tend to be healthier and more successful. They possess effective leadership skills and achieve greater professional success compared to their peers with limited emotional intelligence. The study also examines the relationship between emotional intelligence and the ranking of gymnasts' performances on the floor exercise in artistic gymnastics. The research problem lies in the existence of influential psychological phenomena, both positive and negative, that have not been scientifically studied in the sports field and rely on the subjective analysis of coaches and athletes. Therefore, it is essential to focus on this category of gymnasts, highlighting and studying them in depth. One of the specific objectives of the research is to identify the emotional intelligence of artistic gymnasts. The researchers used a descriptive, correlational approach, deemed suitable for the research problem. This approach encompassed the research methodology and field procedures. The descriptive survey method was employed, appropriate to the nature of the problem. The research population consisted of 124 gymnasts from clubs and training centers, while the research sample comprised 58 gymnasts, representing 46% of the original population. Gymnastics training centers were established, and seven gymnasts from the Diyala Governorate team were excluded from the pilot study. After reviewing several emotional intelligence scales, the researchers selected the emotional intelligence scale developed by Salima Abdullah Alwan (2014) and used statistical analysis to obtain the results. The researchers concluded that there is a variation in emotional intelligence among gymnasts in Iraq and recommend enhancing the emotional intelligence of artistic gymnasts based on scientific principles.
Keywords: Emotional intelligence; ranking players results